Gastrodin improves neuroinflammation-induced cognitive dysfunction in rats by regulating NLRP3 inflammasome - Xue Zheng; Taowu Gong; Chunchun Tang; Yuanping Zhong; Lu Shi; Xu Fang; Dongqin Chen; Zhaoqiong Zhu (BMC Anesthesiology, 2022)
Abstract Neuroinflammation is the main pathological mechanism of cognitive dysfunction caused by neurodegenerative diseases, and effective preventive and therapeutic measures are not available. We predicted the key targets of gastrodin’s effects upon neuroinflammation through Network Pharmacology and molecular docking. Then the predicted targets were used to study how gastrodin affected cognitive dysfunction triggered by lipopolysaccharide-induced neuroinflammation in rats and its mechanisms. Three-month-old male rats were intraperitoneally injected with lipopolysaccharide for 3 days (d), 7 d and 14 d respectively. Gastrodin improved learning and memory ability of rats with neuroinflammation. Lipopolysaccharide enhanced the levels of pro-inflammatory cytokines, such as TNF-α, IL-1β and IL-6, in rat hippocampus, which could be reversed by gastrodin. Gastrodin also inhibited the activation of microglia. Our findings suggested that gastrodin exerted neuroprotective effects in rats with neuroinflammation by impacting the TLR4-NF-kB-NLRP3 pathway. Therefore, gastrodin may be a potential therapeutic agent for neuroinflammation-induced cognitive dysfunction.